Massive pleural effusion due to heart failure in an undetected diabetic hypertensive patient: A case report - Aprilia, Citra Ayu; Aulia, Rizka Dwi; Wibowo, Arif Eko; Permatasari, Evy Novita; Bakhri, Samsul; Abdurrahman, Abdurrahman (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Pleural effusion is pathological accummulation of pleural fluid. The most common causes of pleural effusion are cancer, pneumonia, pulmonary embolism and heart failure. Diabetes mellitus and hypertension are two risk factors of heart failure. A 74-year-old male patient came to the emergency room feeling fatigued all over the body since seven days before, dyspneu and notable reduced appetite and weight loss. Initial vital examination revealed an increase in heart rate and blood pressure (BP=140/80 mmHg, 120 bpm). Oxygen saturation was normal and deteriorate from time to time (92.5%). Chest physical examination showed pleural effusion on the right lungs. Laboratory findings noted an elevated blood glucose and mild hypokalemia in patients. ECG result showed old myocardial infact (OMI) anteroseptal and infrequent premature ventricular contraction (PVC). Chest X-Ray revealed a massive pleural effusion on the right lugs, a mediastinal shift and cardiomegaly. The patient were given IVFD RL, gliquidone, Lantus Bisoprolol, B-Complex, and also thoracentesis for the pleural effusion. The underlying pathology largely determines the clinical symptoms of pleural effusion. In this case, the most probable underlying cause is heart failure. The risk factors of heart failure, in this case, are undetected diabetes melitus, hypertension, OMI and arrythmia. Increasing prevention and early detection of chronic illness such as diabetes melitus and hypertension is a very necessary step.